Predicting Global Functional Outcomes Among Post-traumatic Epilepsy Patients After Moderate-to-Severe Traumatic Brain Injury: Development of a Prognostic Model - Yu, Tingting; Liu, Xiao; Sun, Lei; Lv, Ruijuan; Wu, Jianping; Wang, Qun (Frontiers in Neurology, 2022)
Objective: The development of post-traumatic epilepsy (PTE) following traumatic brain injury (TBI) is associated with unfavorable functional outcomes, and the global function of PTE patients might change dynamically overtime. Predicting the long-term functional outcomes of patients with PTE may help to develop accurate rehabilitation programs and improve their qualities of life. Based on this, the objective of this study is to use clinical data to derive and validate a model for predicting the functional outcomes of patients with PTE after moderate-to-severe TBI. Methods: This study retrospectively analyzed 721 patients with PTE after moderate-to-severe TBI in the Epilepsy Centre, Beijing Tiantan Hospital, from January, 2013 to December, 2018. All patients had favorable global function as indicated by the Glasgow Outcome Scale-Extended (GOSE) at the time of their first late post-traumatic seizure (PTS) onset, and the 5-year global function after first late PTS onset was chosen as the principal outcome of interest. To identify possible predictors for global functional outcome, univariate and multivariate logistic regression techniques were used. A prognostic model was established using these identified predictors, the internal validation with bootstrapping method was performed, and the model was then visualized as a graphical score chart. Results: The 5-year global functional outcome of 98 (13.59%) patients was unfavorable, and the temporal lobe lesion was found as the strongest predictor of unfavorable outcome. The final prognostic model also included the following other predictors: gender, age at TBI, multiple injuries, severity of TBI, and latency of PTE. Discrimination was satisfactory with C-statistic of 0.754 (0.707 - 0.800), the goodness-of-fit test indicated good calibration (P = 0.137), and the C- statistic was 0.726 for internal validation. A graphical score chart was also constructed to provide the probability of unfavorable 5-year global functional outcome more readily. Conclusions: Clearer treatment strategies are essential to help ameliorate the global functional outcomes of patients with PTE. Our proposed prognostic model has significant potential to be used in clinic for predicting global functional outcome among patients with PTE after moderate-to-severe TBI.